Persepsi Konsumen Terhadap Pasar Tradisional (Studi Kasus pada Pasar Keramat Tinggi Muara Bulian) - Ahmad Fithoni; Nur Fadillah (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study was to determine consumer perceptions of product prices, service levels, product quality, physical environment, market location, the diversity of goods in the Muara Bulian high sacred market. This type of research is descriptive research using a quantitative approach. This study will explain consumer perceptions of the variables to be studied, namely variables of product prices, service levels, product quality, physical environment, location and diversity of products sold. In this study, the population is consumers who shop and are around the Keramat Tinggi market area, namely the people of Pasar Baru Village and the Sridadi Society totaling 100 respondents, The results showed that consumer perceptions of product price variables were classified as competitive. The service level is classified as satisfactory. The product quality is good. The physical environment is quite good. The location is classified as strategic, while the diversity of goods in the Muara Bulian sacred high market is good.